Vagus nerve stimulation for the therapy of Dravet syndrome: a systematic review and meta-analysis - Chen, Shuang; Li, Man; Huang, Ming (Frontiers in Neurology, 2024)
Objective Dravet syndrome (DS) is a refractory developmental and epileptic encephalopathy characterized by seizures, developmental delay and cognitive impairment with a variety of comorbidities, including autism-like behavior, speech dysfunction, and ataxia. Vagus nerve stimulation (VNS) is one of the common therapies for DS. Here, we aim to perform a meta-analysis and systematic review of the efficacy of VNS in DS patients. Methods We systematically searched four databases (PubMed, Embase, Cochrane and CNKI) to identify potentially eligible studies from their inception to January 2024. These studies provided the effective rate of VNS in treating patients with DS. The proportions of DS patients achieving ≥50% reduction of seizure frequency were extracted from these studies. Meta-analyses were performed to respectively evaluate the efficacy of VNS for DS after 3, 6, 12, 18, 24 and 36 months. Results Sixteen trials with a total of 173 patients were included. Meta-analyses showed that the pooled efficiency was 0.54 (95% CI 0.43–0.65) in the DS patients treated with VNS (p < 0.05). Meanwhile, the pooled efficiency respectively was 0.42 (95% CI 0.25–0.61), 0.54 (95% CI 0.39–0.69), 0.51 (95% CI 0.39–0.66), and 0.49 (95% CI 0.36–0.63) in the DS patients treated with VNS after 3, 6, 12 and 24 months (p < 0.05). Conclusion This study suggests that VNS is effective in the treatment of DS. However, few studies have focused on VNS for DS, and there is a lack of high-quality evidence. Thus, high-quality randomized controlled trials are needed to confirm the efficacy of VNS in DS.